"Glued to the Tube": The Interplay Between Self-Control, Evening Television Viewing, and Bedtime Procrastination. (June 2021) - Exelmans, Liese; Van den Bulck, Jan
There is ample evidence that media use displaces sleep, but little theory about the mechanism that explains this. We studied sleep displacement as a self-control issue: People postpone going to bed because they have trouble ending their media exposure. We therefore modeled television viewing (habitual viewing, deficient TV self-regulation, and viewing volume) as a mediator of the effect of trait self-control on bedtime procrastination. A random sample of 821 adults participated in face-to-face interviews using standardized questionnaires. Lower self-control was associated with more bedtime procrastination. This relationship was mediated by habitual viewing, which led to less bedtime procrastination, and deficient TV self-regulation, which led to more bedtime procrastination. Evening viewing volume was not a significant mediator. Our results support the idea that (1) self-regulatory failure over television viewing can partly explain the common struggle with bedtime, and (2) strong viewing habits seem to inhibit bedtime procrastination.